Design and Development of Web-Based Foodbank Management System by Using Waterfall Approach - LOO, ZHI XIN; ABD ISHAK, SUHAIMI (Applied Information Technology And Computer Science, 2023)
According to the Solid Waste Management and Public Cleansing Corporation (SWCorp), Malaysians produce a large amount of food waste which can fill seven Olympic swimming pools every day. The objectives of this system are to design a food bank management system based on user requirements, develop the food bank management system which contains a module for donators, a module for food and a module for food recipients using PHP and MySQL database and test all the modules and functions of the developed food bank management system. PHP and MySQL database are used to conduct the study. Imagining and determining what the final outcomes will be is the suggestion for future work.